2017
DOI: 10.1038/s41598-017-18469-6
|View full text |Cite|
|
Sign up to set email alerts
|

Entropy is a Simple Measure of the Antibody Profile and is an Indicator of Health Status: A Proof of Concept

Abstract: We have previously shown that the diversity of antibodies in an individual can be displayed on chips on which 130,000 peptides chosen from random sequence space have been synthesized. This immunosignature technology is unbiased in displaying antibody diversity relative to natural sequence space, and has been shown to have diagnostic and prognostic potential for a wide variety of diseases and vaccines. Here we show that a global measure such as Shannon’s entropy can be calculated for each immunosignature. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…3B ), which further validated our assumptions since lymphoma evolves from a single population of lymphocytes. Another report also demonstrated that lymphoma had a distinct humoral profile compared to other cancer types 19 .…”
Section: Resultsmentioning
confidence: 97%
“…3B ), which further validated our assumptions since lymphoma evolves from a single population of lymphocytes. Another report also demonstrated that lymphoma had a distinct humoral profile compared to other cancer types 19 .…”
Section: Resultsmentioning
confidence: 97%
“…We asked whether information theory could provide some insight into the behavior of the monoclonals. Here we used Shannon's entropy [17] to explore how many independent binding events could be examined together to form a picture of antibody behavior. When examined along with the histograms of the data, a picture emerges of how a given antibody responds to random sequences.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the entropy score for an immunosignature increases (more randomness) as additional monoclonals were added to the solution that bound to the microarray. Thus, for a single monoclonal, an entropy score would be high if that monoclonal were more promiscuous, but also a strong binder [17]. The antibody p53 Ab8 had the highest relative entropy score across all libraries and has shown strong and very specific binding to very few peptides, generally…”
Section: Immunosignature Training On 24 Monoclonalsmentioning
confidence: 99%
See 2 more Smart Citations